Managerial Views of Supply Chain Collaboration: An Empirical Study - Sridharan, Ramaswami; Simatupang, Togar M (Gadjah Mada International Journal of Business, 2009)
Â  This paper is carried out to empirically examine managerial perceptions on the relationship between supply chain collaboration practice and operational performance. The framework suggests that collaborative practice is characterised by three distinct factors: (1) decision synchronisation, (2) information sharing, and (3) incentive alignment, which enable the chain members to effectively match supply with customer demand. An important question is whether or not collaborative practice leads to better operational performance. A survey research was employed to assess the relationship between collaborative practice and operational performance of New Zealand companies. The survey results show significant positive impacts of key factors of collaborative practice on operational performance. The findings suggest that information sharing, decision synchronisation, and incentive alignment are important determinants of operational performance. This study demonstrates that the chain members need to understand the role of different key factors of collaborative practice that can be redesigned to leverage operational performance.